Targeting antitumor CD4 helper T cells with universal tumor-reactive helper peptides derived from telomerase for cancer vaccine - Adotévi, Olivier (Landes Bioscience, 2013)
Current cancer immunotherapies predominantly rely on CD8(+) T cells to fight against tumors. However accumulative evidence showed that proinflammatory CD4(+) helper T cells are critical determinants of effective antitumor immunity. The utilization of universal tumor-reactive helper peptides from telomerase represents a powerful approach to the fully use of CD4(+) T cell-based immunotherapy.